An uncommon cause of abdominal mass: Phytobezoar - Khadka, Dibas; Karki, Binod; Thapa, Suresh; Shrestha, Barun (Medical Journal of Shree Birendra Hospital, 2017)
Phytobezoar is a gastric foreign body formed due to accumulation of ingested fruits and/or vegetables. Patients usually have a predisposing condition leading to alteration in gastric emptying. Altered gastric emptying leads to stagnation and amalgamation of the ingested vegetables or fruits. This condition can be easily diagnosed with upper gastrointestinal endoscopy. Management is medical if the size is small. Larger phytobezoars need endoscopic therapy. In this case report, we describe a case of phytobezoar in a middle aged lady with no known risk factor. She was managed successfully by therapeutic endoscopy.